2023
DOI: 10.1111/pace.14687
|View full text |Cite
|
Sign up to set email alerts
|

Association of abnormal p‐wave parameters with brain MRI morphology: The atherosclerosis risk in communities neurocognitive study (ARIC‐NCS)*

Abstract: BackgroundRecent evidence indicates that abnormal P‐wave parameters (PWPs)—ECG markers of atrial myopathy—are associated with incident dementia, independent of atrial fibrillation (AF) and clinical ischemic stroke. However, the mechanisms remain unclear and may include subclinical vascular brain injury. Hence, we evaluated the association of abnormal PWPs with brain MRI correlates of vascular brain injury in the Atherosclerosis Risk in Communities Neurocognitive Study (ARIC‐NCS).MethodsARIC‐NCS participants wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The resulting neurovascular dysfunction and inflammation can impair glymphatic clearance and exacerbate existing AD pathology leading to synaptic dysfunction and eventually brain atrophy (Moore and Jefferson 2021). A recent study by (Reyes et al 2023) found an association between prolonged PWD and various cerebrovascular related injuries, but not with gross lobar volumes. We, on the other hand, found a significant association between short PWD and accelerated brain aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting neurovascular dysfunction and inflammation can impair glymphatic clearance and exacerbate existing AD pathology leading to synaptic dysfunction and eventually brain atrophy (Moore and Jefferson 2021). A recent study by (Reyes et al 2023) found an association between prolonged PWD and various cerebrovascular related injuries, but not with gross lobar volumes. We, on the other hand, found a significant association between short PWD and accelerated brain aging.…”
Section: Discussionmentioning
confidence: 99%
“…Anomalies in PWD, whether shorter or longer than the norm, are believed to reflect structural or physiological alterations in the left or right atria. These subtle variations thus provide markers of cardiac pathology and can serve as early indicators of various cardiovascular diseases, including AF and other arrhythmias, cardiovascular risk factors and related deaths (He et al 2017, Nielsen et al 2015, Magnani et al 2009, Kosar et al 2008, Uyarel et al 2005, Magnani et al 2015, and more recently dementia (Gutierrez et al, 2019) and cerebrovascular-related injuries (Reyes et al 2023).…”
Section: Introductionmentioning
confidence: 99%